The Church, Faith and Religion in the System of Charlemagne’s Rule - Stępień, Jakub (Prawo Kanoniczne, 2025)
The rule of Charlemagne left a lasting impact on the history of Europe in every aspect of – not only medieval – societies’ functioning. The inspiration of the monarch’s actions can also be seen in the political and legal history of Europe, in terms of the way of exercising power by subsequent monarchs. The alliance of the ruler of the Carolingian dynasty with the Roman Church played an extremely important role in the effective implementation of his competences – church institutions, as well as Christian doctrine and tradition were the key elements in the process of legitimizing and consolidating power of the Frankish monarch. The close connection of the tiara and the crown within Charlemagne’s system of government had a number of consequences, also for the current discourse on the relationship between religious and political communities.